Genotyping in Sickle Cell Disease Patients: The French Strategy - Floch, Aline (Transfus Med Hemother, 2018)
This review presents the French strategy for blood group genotyping in high-responder and newly diagnosed sickle cell disease (SCD) patients. In addition to FY, JK, and MNS genotyping, the RH blood group system is now explored in SCD patients in France. Molecular typing has been used for the deduction of partial RH2 (C) antigens since 2010, and the gradual implementation of systematic RHD and RHCE genotyping nationwide was initiated in late 2014. In our laboratory, 962 RH:2 (C-positive) SCD patients have been tested since 2010, and 1,148 SCD patients of all RH phenotypes have been genotyped for clinically relevant alleles of RHD and RHCE since late 2014.